2017
DOI: 10.1136/bmjopen-2017-017012
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Concussion Assessment in Pediatrics (A-CAP): a prospective, concurrent cohort, longitudinal study of mild traumatic brain injury in children: study protocol

Abstract: IntroductionPaediatric mild traumatic brain injury (mTBI) is a public health burden. Clinicians urgently need evidence-based guidance to manage mTBI, but gold standards for diagnosing and predicting the outcomes of mTBI are lacking. The objective of the Advancing Concussion Assessment in Pediatrics (A-CAP) study is to assess a broad pool of neurobiological and psychosocial markers to examine associations with postinjury outcomes in a large sample of children with either mTBI or orthopaedic injury (OI), with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 71 publications
1
73
0
Order By: Relevance
“…AD, axial diffusivity; BA, Brodmann area; CP, cerebral peduncles; CR, corona radiate; RD, radial diffusivity. 26 The data presented here suggest that they may not provide useful information with which to predict recovery from mTBI in children and/or adolescents.…”
Section: Mrsmentioning
confidence: 78%
See 1 more Smart Citation
“…AD, axial diffusivity; BA, Brodmann area; CP, cerebral peduncles; CR, corona radiate; RD, radial diffusivity. 26 The data presented here suggest that they may not provide useful information with which to predict recovery from mTBI in children and/or adolescents.…”
Section: Mrsmentioning
confidence: 78%
“…The identification of the brain biomarkers of pediatric mTBI will enable the quantification of the impact of an injury and trajectory of recovery. 13,26 This will directly inform future research and the impact of persistent post-mTBI symptoms, which may help refine return-toactivity decision-making and assist in the development of effective interventions.…”
mentioning
confidence: 99%
“…The present study is being conducted at a single site, the RCH (a paediatric tertiary hospital). While the presentation of concussion is significant at RCH (~1000 per year), it is possible that this will limit the recruitment options relative to other studies (eg, A-CAP)44 and reduce statistical power.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Similarly, consequences of injury such as not being able to participate in normal daily activities can impact outcomes. Therefore, some studies have opted to use an orthopedic injury (OI) cohort as the control group, as it shares traumatic event exposure and the associated recovery, can be recruited using a similar recruitment pathway (i.e., presentation in emergency rooms), as well as other factors that are non-specific to brain injury but mediate recovery (Yeates et al, 2017(Yeates et al, , 2009. However, this practice has been called into question as some studies have shown no clear advantage over community controls (Beauchamp, Landry-Roy, Gravel, Beaudoin, & Bernier, 2017;Mathias, Dennington, Bowden, & Bigler, 2013).…”
Section: Control Subjectsmentioning
confidence: 99%
“…When developing multisite studies, one option is to use human phantoms and scan the same individuals at all sites to at least be able to quantify and understand the differences in metabolite quantification. This approach was recently used in a 5-site child and adolescent concussion study (Yeates et al, 2017). Nonetheless, at the present time, MRS findings from multisite studies have been limited (Vagnozzi et al, 2010) e. Selected volume size and location: minimum of 6 cm 3 placed in the frontal white matter ( Figure 6).…”
Section: Multisite Studies and Enigmamentioning
confidence: 99%